Cartography in Central and Eastern Europe CEE 2009 - Gartner, Georg; Ortag, Felix; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The region of Central and Eastern Europe has a rich and long history in cart- raphy. Many important improvements in mapping and cartography have been proposed and performed by cartographers and researchers of that region. The long and outstanding history has led to a lively and vivid presence. Now contemporary methods for depicting the earth and its cultural and natural attributes are used. This book focuses on the contemporary activities in all major realms of cartography in Central and Eastern Europe. It covers aspects of theoretical, topographical, thematic and multimedia cartography, which have been presented at the frst Symposium on Cartography for Central and Eastern Europe, which took place from February 16th to 17th, 2009 in Vienna, Austria and was organized by the International Cartographic Association (ICA) and the Vienna University of Technology. The symposium$1 (Bs aim was to bring together cartographers, GI scientists and those working in related disciplines from CEE with the goal of offering a platform for discussion and exchange and stimulation of joined projects. About 130 scientists from 19 countries followed the invitation and visited Vienna, Austria. A selection of fully reviewed contributions is edited in this book and is meant as a mirror of the wide range of activities in the realm of cartography in this region. The innovative and contemporary character of these topics has lead to a great variety of interdis- plinary contributions. Topics cover an enormous range with heterogenous relati- ships to the main book issues.s
From Ortelius to OpenStreetMap #x2013; Transformation of the Map into a Multifunctional Signpost -- Topographic Mapping -- EuroRegionalMap #x2013; How to Succeed in Overcoming National Borders -- Methods of Portraying Spatial Data Used in Official Geoinformation Services in Poland #x2013; A Comparative Study -- Compilation of Digital Elevation Model for Turkey in 3-Arc-Second Resolution by Using SRTM Data Supported with Local Elevation Data -- Mapping Land Cover with Commercial and Freeware Image Classification Software #x2013; An Example from Bavaria, Germany -- New Approach to Multi Scale Cartographic Modelling of Reference and Thematic Databases in Poland -- Implementation of the INSPIRE-Directive in Germany and Poland #x2013; Legal Point of View -- Cartographic Modelling -- Automated Building Simplification Using a Recursive Approach -- Constraint-Based Evaluation of Automated and Manual Generalised Topographic Maps -- Cross-Border Mapping: Geodata, Geonames, Multilinguality and More -- XSLT Templates for Thematic Maps -- Geoinformational Methods in Ecodiagnostical Studies for the Losiny Ostrov National Park Territory -- Cartography and Graphic Design -- Various Ways of Assessment of Cartographic Works -- Multimedia Cartography -- Exploring Space: Applying Interactive Integrated Media for Visualising Geography -- The Art of Autostereoscopic Relief Representation in Cartography -- Approaches to Image Abstraction for Photorealistic Depictions of Virtual 3D Models -- Globes on the Web #x2013; Technical Background and First Items of the Virtual Globes Museum -- Mapping Crime Using Geovirtual Urban Environments -- A Survey of Mobile Indoor Navigation Systems -- Atlas Cartography -- Mapping Space-Related Transformation Processes in Eastern Europe. Examples from the Atlas of Eastern and Southeastern Europe -- The Demographic Atlas of Croatia #x2013; A Web-Based Atlas Information System -- Mapping and Analysing the Local Language Areas for Slovenian Linguistic Atlas -- Interactive and Multimedia Atlas Information Systems as a Cartographic Geo-Communication Platform -- Cartographic Applications -- Integration of Hightech Components for Operating Ragweed Mapping and Control System in Hungary Using Remote Sensing and GIS -- Detailed Mapping of Landslide Susceptibility for Urban Planning Purposes in Carpathian and Subcarpathian Towns of Romania -- Dynamic Cartographic Methods for Visualisation of Health Statistics -- A Multiresolution, Reference and Thematic Database as the NSDI Component in Poland #x2013; The Concept and Management Systems -- The Remote Sensing Based Hungarian Crop Production Forecast Program (Cropmon) and its Other Applications -- The Blind Mouse #x2013; A Game for Developing and Popularizing Cartographical Skills -- Historical Cartography -- Orientation of the Map of Lazarus (1528) of Hungary #x2013; Result of the Ptolemian Projection? -- History of the Hungarian Geological Maps #x2013; An Overview from the 18 Century to Nowadays -- Cartometric Analysis of Old Maps on the Example of Vogt#x2019;s Map -- Structural Lineaments Derived from Planforms of Watercourses in the Second Military Survey of the Habsburg Empire -- The Austro-Hungarian Triangulations in the Balkan Peninsula (1855#x2013;1875) -- Maps of Czech Lands in the Period 1518#x2013;1720 from the Map Collection of Charles University in Prague -- The Dilemma for the History of Modern Maps Based on Neo-Cartographic Technologies.
Keywords: Geography; Earth sciences; Geophysics; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Earth Sciences, general; Geophysics/Geodesy.; Electronic books